2017
DOI: 10.1038/s41598-017-02350-7
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption Performance of Encapsulated Candida krusei for the removal of Copper(II)

Abstract: The use of microorganisms in biosorption is one of the most promising ways to remove trace amounts of heavy metal ions. Nevertheless, the enhancement of the successful removal of heavy metal ions by using different combinations of biosorbents is not generally guaranteed which leaves room to explore the application of the technique. In this study, the performance of free and immobilized forms of a yeast strain, Candida krusei (C. krusei), and calcium alginate (CaAlg) are evaluated for their ability to remove co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 37 publications
(17 reference statements)
1
19
0
Order By: Relevance
“…3C). 25 Besides the corresponding characteristic absorption peaks, the symmetric and asymmetric stretching of C-H at 2947 and 2891 cm À1 were observed. The characteristic peaks of 3,6-anhydro-L-galactose skeletal banding was observed at 931, 894 and 770 cm À1 in composite AG-CH scaffold, which conrms the presence of agarose.…”
Section: Ftir Spectroscopy and Thermal Property Of Scaffoldmentioning
confidence: 97%
See 1 more Smart Citation
“…3C). 25 Besides the corresponding characteristic absorption peaks, the symmetric and asymmetric stretching of C-H at 2947 and 2891 cm À1 were observed. The characteristic peaks of 3,6-anhydro-L-galactose skeletal banding was observed at 931, 894 and 770 cm À1 in composite AG-CH scaffold, which conrms the presence of agarose.…”
Section: Ftir Spectroscopy and Thermal Property Of Scaffoldmentioning
confidence: 97%
“…25 In brief, glutaraldehyde-crosslinked AG-CH scaffold was dried ($10 mg dried mass) at 60 C for 4 h. The scaffold was then ground using mortar-pestle and suspended in 5 mL of ultra pure H 2 O. Zeta potential analysis.…”
Section: Physico-chemical Characterization Of Scaffoldsmentioning
confidence: 99%
“…These results are similar to those reported for Pichia jadinii M9 and Pichia anomala M10. More rapidly with an increment in temperature, with an optimum value of 30°C [33], in the removal of copper for encapsulated Candida krusei [34], and for C. neoformans, with a maximum adsorption capacity for Cr(VI) ion was observed at 28°C [18]. When the temperature increases, the rate of removal of Cr(VI) increases and the contact time required for complete removal of the metal decreases, increasing the redox reaction rate [35].…”
Section: Effect Of the Temperaturementioning
confidence: 99%
“…Yeasts which are used in the enzymatic industry and medicine can survive in a medium containing low or high concentrations of heavy metals (Cottet et al 2020). One of the most important microbial source for biosorption of heavy metals is Candida species (Luna et al 2016), which were shown to play an important role in the accumulation of metal ions (Honfi et al 2016, Luk et al 2017. Metal uptake capacity of Candida species under various experimental conditions depends on the metal type and the yeast species itself (Legorreta-Castañeda et al 2020).…”
Section: Introductionmentioning
confidence: 99%